Cloning of a cellulolytic gene from rumen bacteria using pUC18 vector - VIJAYARANI, VIJAYARANI; VELMURUGAN, R; NACHIMUTHU, K; PADMANABAN, V D (The Indian Journal of Animal Sciences, 2013)
The present work describes the cloning of a cellulolytic gene from the rumen bacteria Ruminococcus albus using pUC18 vectors. In pUC18 cloning, 3 white recombinant colonies with cellulase activity by congo red assay was obtained out of 68 colonies screened. Out of 3 colonies, 1 has a 1.4 kb Hind III insert resembling endoglucanase gene. The homology between the cloned product and genomic DNA of R. albus was checked by dot-blot hybridization. Expression of the gene was tested by growing the recombinant cells in media containing cellobiose and carboxymethyl cellulose.